Tradisi Siat Tipat Bantal Di Desa Kapal, Badung Sebagai Sebuah Daya Tarik Wisata - Ida Bagus Gede Paramita; Ida Bagus Naba (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
Tradition has an important meaning for society. This tradition has cultural values which consist of conceptions that live in the minds of some members of society, regarding things that they must consider very valuable in life. It is the same as the tradition of Siat tipat bantal in the traditional village of Kapal. This tradition is considered very valuable in people's lives because people carry out this tradition, are believed to bring prosperity to their lives and will be free from harvest famine. This article aims to find out the source of the implementation of the Siat tipat bantal tradition which is carried out in the village of Kapal, Badung Regency; to examine the meaning of the ritual behind the implementation of the Siat Tipat Pillow tradition; and studying the tradition of Siat tipat bantal as a tourist attraction in the village of Kapal, Badung district. This research is a qualitative research using a structured approach which is used to study the structure of the practical awareness of the people of the ship who practice the traditional practice of Siat tipat bantal as a routine every year. The data collection method in this article is literature study. The results of this research are knowing the source, meaning of the Siat tipat bantal tradition and studying a tradition that is used as a tourist attraction.Keywords: Tradition, Siat tipat bantal, Tourist Attraction